Conceptualizing the Research Subject with SORKC: Exploring the Mental Health and Well-Being of Forced Migrants from Ukraine - Spitsyna, Larysa Valeriivna (Journal of Educational, Health and Community Psychology, 2025)
The war in Ukraine has led to a humanitarian crisis and widespread suffering, with forced migration—both within and beyond the country's borders—being one of the most significant consequences. Numerous studies highlight the negative effects of war, particularly the prevalence of mental health disorders such as anxiety, acute stress reactions, depression, cognitive impairments, personality disorders, and PTSD. A key innovation of our study is the proposed application of the SORKC model in developing a strategy for data collection. This approach allows the collected data to be structured in a way that facilitates psychotherapeutic or counseling interventions within the cognitive-behavioral framework. Apart from direct conflict-related trauma, forced migrants endure severe stress caused by displacement and uncertain, prolonged journeys seeking safety. Upon arrival in a new country, they often face acculturation stress, also known as post-migration stress. At this stage of the study, we conducted a scientific-theoretical analysis to examine the most widely used operationalizable approaches in contemporary research on forced migrants' mental health. Our goal was to identify an optimal conceptual framework—based on the SORKC model—for understanding the components of well-being and mental health challenges among forced migrants. Based on these insights, we developed an online questionnaire that integrates standardized self-report measures with several sets of open-ended questions, discussed below. The situation of Ukrainian refugees living in Switzerland and other European countries can be stabilized through initial support services. Understanding the challenges they face and identifying those at risk of mental health problems is crucial. The use of the SORKC model as a foundation for assessing an individual’s mental state integrates all essential components: personality variables, situational factors, internal representations of experiences, behavioral reactions, and consequences. This comprehensive approach can significantly enhance the quality of psychotherapeutic services, improve access to mental health care, and provide appropriate support for forced migrants.